Microbially-induced mineral scaling in desalination conditions: Mechanisms and effects of commercial antiscalants. (15th July 2020) - Ansari, Ali; Peña-Bahamonde, Janire; Fanourakis, Sofia K.; Hu, Yandi; Rodrigues, Debora F.
Abstract: Reverse osmosis (RO) technology is promising in the sustainable production of fresh water. However, expansion of RO use has been hindered by membrane fouling, mainly inorganic fouling known as scaling. Although membrane mineral scaling by chemical means have been investigated extensively, mineral scaling triggered by microbial activity has been largely neglected. In this study, the simultaneous biomineralization of CaCO3 and CaSO4 in the presence of three different microbial communities from fresh water, wastewater, and seawater was investigated. In the presence of either 13 or 79 mM of Ca 2+ and SO4 2- in the media, the fresh water microbial community produced calcite/vaterite and vaterite/gypsum, respectively; the wastewater community produced vaterite and vaterite/gypsum, respectively; and the seawater community produced aragonite in both conditions. The results showed that the concentration of salts and the microbial composition influence the types of precipitates produced. The mechanisms of crystal formation of CaCO3 and gypsum by these communities were also investigated by determining the need for metabolic active cells, the effect of a calcium channel blocker, and the presence of extracellular polymeric substances (EPS). The results showed that metabolically active cells can lead to production of EPS and formation of Ca 2+ gradient along the cells through calcium channels, which will trigger formation of biominerals. The prevention of biomineralization by these consortia was also investigated with two common polymeric RO antiscalants, i.e. polyacrylic acid (PAA) and polymaleic acid (PMA). Results showed that these antiscalants do not prevent the formation of the bio-precipitates suggesting that novel approaches to prevent biomineralization in RO systems still needs to be investigated. Graphical abstract: Image 1 Highlights: Microbial consortia can induce biomineralization in RO conditions. The types of crystals formed depend on the microbial diversity. Calcium channels allows Ca 2+ accumulation around cell walls and biomineralization. EPS facilitates biomineralization without cells. Biomineralization cannot be inhibited in the tested conditions by two antiscalants.